Patients' opinions on outcomes following critical illness. Issue 4 (7th January 2018) - Nedergaard, H. K.; Haberlandt, T.; Reichmann, P. D.; Toft, P.; Jensen, H. I.
Abstract : Background: Our aim was to explore which outcomes are most important to patients following ICU‐discharge, and to explore whether intensive care unit (ICU)‐nurses and anesthesiologists are aware of patients' priorities. Methods: First, interviews with adult ICU‐survivors were conducted until data saturation was achieved (10 interviews), and six areas with 36 items were identified. Second, interviews with another eight ICU‐survivors were conducted, narrowing the list to 20. Finally, patients (inclusion criteria: consecutive adults, medical and surgical, ICU‐admission > 5 days, 2–8 months post‐ICU discharge) rated the items, as did ICU‐nurses and anesthesiologists. Results: A total of 32 patients participated (44% women, medians: age 70.5, time since discharge 179 days, length of stay in ICU 9 days, APACHEII 19.5). The three most important outcomes defined by patients were: lack of physical strength, fatigue, and decreased walking distance. The top three for ICU‐nurses (54 participants) were: fatigue, difficulties concentrating, sadness/depression, and for anesthesiologists (17 participants): fatigue, difficulties in activities of daily living, and lack of physical strength. Conclusion: Patients chose lack of physical strength, fatigue, and decreased walking distance as the three most important outcomes following critical illness. Physicians had a higher focus on these physical impairments than ICU‐nurses.